Impact of primary healthcare providers' initial role security and therapeutic commitment on implementing brief interventions in managing risky alcohol consumption: a cluster randomised factorial trial. (December 2015) - Keurhorst, M.; Anderson, P.; Heinen, M.; Bendtsen, Preben; Baena, Begoña; Brzózka, Krzysztof; Colom, Joan; Deluca, Paolo; Drummond, Colin; Kaner, Eileen; Kłoda, Karolina; Mierzecki, Artur; et al.
Abstract Background Brief interventions in primary healthcare are cost-effective in reducing drinking problems but poorly implemented in routine practice. Although evidence about implementing brief interventions is growing, knowledge is limited with regard to impact of initial role security and therapeutic commitment on brief intervention implementation. Methods In a cluster randomised factorial trial, 120 primary healthcare units (PHCUs) were randomised to eight groups: care as usual, training and support, financial reimbursement, and the opportunity to refer patients to an internet-based brief intervention (e-BI); paired combinations of these three strategies, and all three strategies combined. To explore the impact of initial role security and therapeutic commitment on implementing brief interventions, we performed multilevel linear regression analyses adapted to the factorial design. Results Data from 746 providers from 120 PHCUs were included in the analyses. Baseline role security and therapeutic commitment were found not to influence implementation of brief interventions. Furthermore, there were no significant interactions between these characteristics and allocated implementation groups. Conclusions The extent to which providers changed their brief intervention delivery following experience of different implementation strategies was not determined by their initial attitudes towards alcohol problems. In future research, more attention is needed to unravel the causal relation between practitioners' attitudes, their actual behaviour and care improvement strategies to enhance implementation science. Trial registration ClinicalTrials.gov:NCT01501552